Mother Goose goes to India - Sehgal, Kabir; Sehgal, Surishtha (Beach Lane Books, 2021)
A collection of fifteen familiar Mother Goose rhymes reset in India, with character names, foods, numbers, and other aspects changed to reflect life in that country. Includes Hindi language terms.